Hubungan Anemia dan Status Gizi dengan Dismenore pada Mahasiswi Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta - Rina Harum Puspita; Muwakhidah Muwakhidah; Dyah Intan Puspitasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Menstruation is a natural process of endometrial shedding when fertilization does not occur, but many women experience it accompanied by menstrual pain, also known as dysmenorrhea. Dysmenorrhea is menstrual pain during menstruation. Anemia and nutritional status are among the risk factors for dysmenorrhea. The purpose of this study was to determine the relationship between anemia and nutritional status with the incidence of dysmenorrhea in female students at the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. The research method used an analytical observational design with a cross-sectional approach. The population consisted of all female students from the 2023 cohort. The sampling technique used was simple random sampling with a sample size of 88 female students. Anemia data were obtained from measuring hemoglobin levels using the cyanmethemoglobin method, nutritional status from calculating Body Mass Index (BMI), and dysmenorrhea was measured using the WaLIDD questionnaire. The results showed that the respondents were mostly 20 years old (42%), had menarche at the age of ≥ 12 years (68%), had no family history of dysmenorrhea (61%), and had a menstrual duration of 4-7 days (80%). Most respondents experienced anemia (51%) and had a normal nutritional status (43%). The statistical test results showed no significant relationship between anemia (p = 0.258) and nutritional status (p = 0.315) with the incidence of dysmenorrhea in female students at the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. The suggestion for female students is to maintain a balanced and nutritious diet to reduce menstrual pain or dysmenorrhea.